Design of thermo-piezoelectric microstructured bending actuators via multi-field asymptotic homogenization. (October 2018) - Fantoni, Francesca; Bacigalupo, Andrea; Paggi, Marco
Highlights: A multi-field asymptotic homogenization technique for thermo-piezoelectric periodic materials is performed. A consistent and exact determination of the overall constitutive tensors of the microstructured material is provided. Characterization of microstructured unimorph and bimorph bender actuators behavior. The effect of the microstructure on the global deflection of the benders has been investigated. Graphical abstract: Abstract: The use of integrated MicroElectroMechanical systems (MEMS) is recently spread thanks to their improved sensitivity, accuracy and reliability. Accurate preliminary computations born from the need of high precision in the manufacturing process of such devices. Piezoelectric materials are broadly employed in this field as direct converters between mechanical and electrical signals and some of these piezoelectric materials show pyroelectric features, which involve thermo-electrical interactions. Pyroelectric bending actuators are analyzed in the present study in plane conditions. They consists of active PZT layers with in-plane polarization and a microstructured composite layer characterized by a periodic microstructure where PZT fibers with an out of plane polarization are immersed in a polymeric matrix. The constitutive law of the composite layer at the mesoscale has been determined by means of a multi-field asymptotic homogenization technique, recently developed for thermo-piezoelectric materials. Overall constitutive equations characterizing the behavior of the microstructured layer at the mesoscale have been derived and the closed form of the overall constitutive tensors has been provided for the equivalent first-order (Cauchy) homogenized continuum. Deflection of unimorph and bimorph bender actuators has been investigated in relation to their geometrical features, exploiting the out of plane piezoelectric properties of the composite layer, which modify the stiffness of the entire bender. An accurate description of benders behavior at the structural length scale is of fundamental importance in order to design devices with high performances. In this regard, the influence of the microstructure on the global response of the actuator is investigated in the present study in order to understand how the composite material can be tailored to meet specific design requirements.